Tidal and sub-tidal sea level variability at the northern shelf of the Brazilian Northeast Region - FROTA,FELIPE F. (2016)
ABSTRACT A characterization of the sea level variability at tidal and sub-tidal frequencies at the northern shore of the Brazilian Northeast shelf for the period 2009-2011 is presented. The sea level data used was obtained from the Permanent Geodetic Tide Network from the Brazilian Institute of Geography and Statistics for the Fortaleza gauge station. Local wind data was also used to assess its effects on the low-frequency sea level variability. The variability of the sea level was investigated by classical harmonic analysis and by morphology assessment over the tidal signal. The low frequencies were obtained by low-pass filtering. The tidal range oscillated with the highest value of 3.3 m during the equinox and the lowest value of 0.7 m during the solstice. Differences between the spring and neap tides were as high as 1 m. A total of 59 tidal constituents were obtained from harmonic analysis, and the regional tide was classified as semi-diurnal pure with a form number of 0.11. An assessment of the monthly variability of the main tidal constituents (M2, S2, N2, O1, and K1) indicated that the main semi-diurnal solar S2 presented the highest variability, ranging from 0.21 to 0.41 m; it was the main element altering the form number through the years. The low frequency sea-level variability is negligible, although there is a persistent signal with an energy peak in the 10-15 day period, and it cannot be explained by the effects of local winds.